The evolutionary roles of nutrition selection and dietary quality in the human brain size and encephalization - Burini, Roberto Carlos [UNESP]; Leonard, William R. (Springer Nature, 2018)
Background: Humans and other primates have evolved particular morphological and biological traits (e.g., larger brains, slower growth, longer-lived offspring) that distinguish them from most other mammals. The evolution of many distinctive human characteristics, such as our large brain sizes, reduced gut sizes, and high activity budgets, suggest major energetic and dietary shifts. Main body: Over the course of the last three million years, hominin brain sizes tripled. It is often taken for granted that the benefit of a larger brain is an increase in “intelligence” that makes us stand out among other mammals, including our nearest relatives, the primates. In the case of humans, brain expansion was associated with changes in diet, foraging, and energy metabolism. The first marked expansion occurred with the appearance of the genus Homo. Improved diet quality, allomaternal subsidies, cognitive buffering [by earlier weaning and longer juvenile periods], reduced costs for locomotion and by cooperative behavior, and reduced allocation to production, all operated simultaneously, thus enabling the extraordinary brain enlargement in our lineage. Conclusion: It appears that major expansion of brain size in the human lineage is the product of synergistically interacting dietary/nutritional and social forces. Although dietary change was not being the sole force responsible for the evolution of large brain size, the exploitation of high-quality foods likely fueled the energetic costs of larger brains and necessitated more complex behaviors that would have selected for greater brain size.
Keywords: Evolutionary foraging; High-quality diet; Human brain evolution; Human encephalization